2022
DOI: 10.1111/ijac.14046
|View full text |Cite
|
Sign up to set email alerts
|

Lateritic soil geopolymer composites for ceramics and engineering construction applications

Abstract: Characterization of an Amazonian, laterite‐doped, kaolinitic soil (LK) or “lateritic soil” and laterite‐doped metakaolin (LMK) calcined at two distinct rates, as well as granite‐marble (GM) particulate industrial wastes was performed by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X‐ray diffraction (XRD), energy dispersive X‐ray fluorescence (XRF) spectrometry, and particle size and distribution analysis. In addition, an LMK geopolymer (GP) and a lateritic metakaolin‐based GP reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…As stated above, both strength, fracture toughness, and fracture work of multilayered composites are significantly improved with respect to the bio‐inspired structure and the resin and fabric content, but the mechanical properties of the porcelain ceramic tiles are poor constrained by the lack of slip systems 24 . It is worth mentioning that the mechanical properties of the biologically inspired composites in this study are even better than those reported for advanced materials in engineering 25–27 . This unique combination of the main properties in this biologically inspired composite emphasizes the importance of complex hierarchical design for strengthening and toughening at multiple length scales, which has great significance in promoting the application levels of low‐performance ceramic materials in bio‐inspired high‐performance composites for actual ceramic manufacturers.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…As stated above, both strength, fracture toughness, and fracture work of multilayered composites are significantly improved with respect to the bio‐inspired structure and the resin and fabric content, but the mechanical properties of the porcelain ceramic tiles are poor constrained by the lack of slip systems 24 . It is worth mentioning that the mechanical properties of the biologically inspired composites in this study are even better than those reported for advanced materials in engineering 25–27 . This unique combination of the main properties in this biologically inspired composite emphasizes the importance of complex hierarchical design for strengthening and toughening at multiple length scales, which has great significance in promoting the application levels of low‐performance ceramic materials in bio‐inspired high‐performance composites for actual ceramic manufacturers.…”
Section: Resultsmentioning
confidence: 54%
“…24 It is worth mentioning that the mechanical properties of the biologically inspired composites in this study are even better than those reported for advanced materials in engineering. [25][26][27] This unique combination of the main properties in this biologically inspired composite emphasizes the importance of complex hierarchical design for strengthening and toughening at multiple length scales, which has great significance in promoting the application levels of low-performance ceramic materials in bio-inspired high-performance composites for actual ceramic manufacturers.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Para Figura 6, ativada a uma concentração de NaOH 8 M, observa-se que com o passar dos dias de cura, há modos vibracionais semelhantes, ou seja, em ~3450 cm⁻ 1 tem-se bandas atribuídas às vibrações O-H [26,27].…”
Section: Espectros Ftir Dos Geopolímerosunclassified
“…Para Figura 7, porém, ativada a 10 M, observa-se que com o passar dos dias de cura, há modos em ~3450 cm⁻ 1 que são atribuídas às vibrações O-H. A banda menos intensa aos 28 Dias de cura, sugere a adsorção das moléculas de água do material [26,27]. Bandas entre 1650 cm⁻ 1 e 1630 cm⁻ 1 são atribuídas às interações fracas de moléculas de H 2 O que são adsorvidas na superfície ou estão presas nas regiões interlamelares da estrutura geopolimérica [28][29][30].…”
Section: Espectros Ftir Dos Geopolímerosunclassified
See 1 more Smart Citation